A Combined Administration of Testosterone and Arginine Vasopressin Affects Aggressive Behavior in Males - Dilsa Cemre Akkoc Altinok; Mikhail Votinov; Friederike Henzelmann; HanGue Jo; Albrecht Eisert; Ute Habel; Lisa Wagels (Brain Sciences, 2021)
Aggressive behavior is modulated by many factors, including personality and cognition, as well as endocrine and neural changes. To study the potential effects on the reaction to provocation, which was realized by an ostensible opponent subtracting money from the participant, we administered testosterone (T) and arginine vasopressin (AVP) or a respective placebo (PL). Forty males underwent a functional magnetic resonance imaging session while performing a provocation paradigm. We investigated differential hormone effects and the potential influence of Machiavellian traits on punishment choices (monetary subtractions by the participant) in the paradigm. Participants in the T/AVP group subtracted more money when they were not provoked but showed increased activation in the inferior frontal gyrus and inferior parietal lobule during feedback compared to PL. Higher Machiavellian traits significantly increased punishing behavior independent of provocation only in this group. The pilot study shows that T/AVP affects neural and behavioral responses during a provocation paradigm while personality characteristics, such as Machiavellian trait patterns, specifically interact with hormonal influences (T/AVP) and their effects on behavior.